2018
DOI: 10.1007/jhep02(2018)009
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement entropy of singular surfaces under relevant deformations in holography

Abstract: In the vacuum state of a CFT, the entanglement entropy of singular surfaces contains a logarithmic universal term which is only due to the singularity of the entangling surface. We consider the relevant perturbation of a three dimensional CFT for singular entangling surface. We observe that in addition to the universal term due to the entangling surface, there is a new logarithmic term which corresponds to a relevant perturbation of the conformal field theory with a coefficient depending on the scaling dimensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 79 publications
3
10
0
Order By: Relevance
“…Moving to quadratic theories, the contributions without anomaly piece modify the charges in the same way as a (6) , whereas the term involving two Riemanns contains an extra piece coming from a contraction of extrinsic curvatures, which in this case reads With respect to the case of smooth regions, the novelty here is the appearance of a new logarithmic divergence controlled by the corner function a(θ), of universal nature. By now, many aspects of this function have been studied in a plethora of contexts -e.g., for free fields [88][89][90][91][92][93][94], for large-N vector models [95], for holographic theories [19,65,73,[96][97][98][99][100][101][102][103][104][105][106], in interacting lattice models [107][108][109][110][111][112][113][114], and for general CFTs [18,[115][116][117][118]. As a result of this thorough study, the function a(θ) has been shown to satisfy a number of properties, universal relations and bounds which we summarize now.…”
Section: Six Dimensionsmentioning
confidence: 99%
“…Moving to quadratic theories, the contributions without anomaly piece modify the charges in the same way as a (6) , whereas the term involving two Riemanns contains an extra piece coming from a contraction of extrinsic curvatures, which in this case reads With respect to the case of smooth regions, the novelty here is the appearance of a new logarithmic divergence controlled by the corner function a(θ), of universal nature. By now, many aspects of this function have been studied in a plethora of contexts -e.g., for free fields [88][89][90][91][92][93][94], for large-N vector models [95], for holographic theories [19,65,73,[96][97][98][99][100][101][102][103][104][105][106], in interacting lattice models [107][108][109][110][111][112][113][114], and for general CFTs [18,[115][116][117][118]. As a result of this thorough study, the function a(θ) has been shown to satisfy a number of properties, universal relations and bounds which we summarize now.…”
Section: Six Dimensionsmentioning
confidence: 99%
“…where a (3) n (Ω) is a cutoff-independent function of the opening angle which has been extensively studied in the literature -e.g., for free fields in [15][16][17][18][19][20][21][22], for large-N vector models in [23], for holographic theories in [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], in interacting lattice models in [40][41][42][43][44][45], and for general CFTs in [46][47][48][49][50].…”
Section: Contentsmentioning
confidence: 99%
“…There are similar stories on the EE of the relevant perturbed conformal field theories [15,41,42,43,44,45,46,47,48]. As is well known, relevant perturbation of a conformal field theory induces a universal logarithmic term in the entanglement entropy, either from the field theoretic calculations in [41,43,44,45] or the holographic computations.…”
Section: Introductionmentioning
confidence: 81%
“…In this article, we extend our previous work [48] and study the effect of relevant perturbation of CFT on the entanglement entropy of higher dimensional singular regions including c n , k × R m and c n × R m , which is possible when either the intrinsic or extrinsic curvatures have singularities [32]. In considering these geometries, we suppose that the background geometry is flat R d , and write the metric in Euclidean signature as…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation